2020
DOI: 10.1111/gcb.14965
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice loss increases genetic isolation in a high Arctic ungulate metapopulation

Abstract: Sea ice loss may have dramatic consequences for population connectivity, extinction–colonization dynamics, and even the persistence of Arctic species subject to climate change. This is of particular concern in face of additional anthropogenic stressors, such as overexploitation. In this study, we assess the population‐genetic implications of diminishing sea ice cover in the endemic, high Arctic Svalbard reindeer (Rangifer tarandus platyrhynchus) by analyzing the interactive effects of landscape barriers and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 99 publications
(175 reference statements)
8
60
0
Order By: Relevance
“…Although our "snapshot-in-time" data call for cautious interpretation, this study adds novel and nuanced insights into how a variety of behavioral strategies may potentially buffer negative effects of a changing winter climate in isolated arctic ungulate populations. The increasing isolation of some coastal reindeer populations, inhabiting islands and peninsulas separated by landscape barriers and a lack of sea ice (Poole et al 2010, Jenkins et al 2018, Peeters et al 2020, makes them particularly vulnerable to changes in snowpack conditions and forage accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our "snapshot-in-time" data call for cautious interpretation, this study adds novel and nuanced insights into how a variety of behavioral strategies may potentially buffer negative effects of a changing winter climate in isolated arctic ungulate populations. The increasing isolation of some coastal reindeer populations, inhabiting islands and peninsulas separated by landscape barriers and a lack of sea ice (Poole et al 2010, Jenkins et al 2018, Peeters et al 2020, makes them particularly vulnerable to changes in snowpack conditions and forage accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Jenkins et al (2016) found a negative temporal trend in landscape connectivity for island-dwelling caribou populations in the Canadian Arctic Archipelago, predicting a further decrease due to future loss of sea ice (see also Mallory and Boyce 2018). In both Svalbard reindeer and arctic island-dwelling caribou (R. t. groenlandicus, R. t. peary), there are strong links between sea-ice dynamics and the level of genetic isolation among populations (Jenkins et al 2018, Peeters et al 2020. This highlights the importance of behavioral plasticity at small spatial scales for population viability in arctic island ungulates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few remaining and critically small populations gradually recolonised the former distribution range, partly mediated by reintroductions (Le Moullec et al 2019b). Landscape genetics analyses further indicated that the spatial population structure was determined by restricted dispersal across steep mountains, glaciers, fjords and open sea between islands (Peeters et al 2020). Furthermore, the seasonal occurrence of sea ice facilitated dispersal and was a key driver of gene flow and source−sink dynamics among populations.…”
Section: Impacts Of Climate Change and Overexploitation On Spatial Po...mentioning
confidence: 99%
“…The lack of sea ice as a dispersal corridor will likely decrease recolonisation probabilities and increase the risk of inbreeding and loss of genetic diversity, particularly in small and isolated populations (Saccheri et al 1998). Peeters et al (2020) demonstrated how population genetic structure and connectivity can be influenced by interactions of past (overexploitation) and ongoing (climate change) anthropogenic drivers. Climate change and harvesting can thus strongly influence the evolutionary potential and persistence of species through effects on population connectivity and spatial genetic struc-ture.…”
Section: Impacts Of Climate Change and Overexploitation On Spatial Po...mentioning
confidence: 99%